MECHANISMS OF BIFIDOBACTERIA RESISTANCE TO LIPOLYTIC ENZYMES OF STAPHYLOCOCCUS AUREUS - YULIYA V. Zakharova; LARISA Y. Otdushkina; LYUDMILA A. Levanova; ANDREY S. Sukhik (Фундаментальная и клиническая медицина)
Aim. To study the mechanisms of Bifidobacteria membrane resistance to the lipases of Staphylococcus aureus. Materials and Methods. Quantitative and qualitative composition of fatty acids in membranes of Bifidobacteria was evaluated before and after exposure to the lipolytic enzymes of S. aureus using gas chromatography-mass spectrometry. Results. Membrane of Bifidobacterium breve consisted of oleic (C 18:1; 80,3 µg), palmitic (C 16:0; 53,9 µg), and linoleic (C 18:2; 29,4 µg) acid, while membranes of B. bifidum and B. longum were composed mainly of palmitic (C 16:0; 21,2 µg and 21,8 µg, respectively) and stearic (C 18:0; 18,8 µg and 11,9 µg, respectively) acid. Upon exposure to the S. aureus lipase, the proportion of saturated fatty acids in the membrane of B. breve increased twofold, with the corresponding sevenfold decrease in unsaturated fatty acids and altered diversity of fatty acid composition. However, this was not the case for the membranes of B. bifidum and B. longum. Conclusions. Mechanisms of Bifidobacteria resistance to the lipolytic enzymes of S. aureus are species-specific. In B. breve, a change in the liquid-crystalline state of the membrane occurs; however, the membranes of B. longum and B. bifidum are resistant to the action of S.aureus lipases due to the high content of saturated fatty acids.